DETERMINASI DIAMOND FRAUD DALAM MENDETEKSI KECURANGAN PADA LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN PERDAGANGAN BESAR SUB SEKTOR BARANG PRODUKSI DAN KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2017-2019) - Heni Yusnita, M.Ak.; Anggun Rizka Utami (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The purpose of this research is to study whether the components of diamond fraud can be used to approve fraudulent financial statements. This study uses a purposive sampling method with 27 companies during the 2017-2019 period. The results of multiple linear regression in SPSS 25 claims for the pressure component can be seen if the hypothesis is accepted relating to financial targets determined by gross profit margins can be used fraud on the company, as well as the opportunity component can also be used for fraud on the financial statements. For the next two components, namely rationalization which is proxied by a change of auditors, the results of the study cannot be used to replace fraud on the financial statements and abilities that are proxied by a change of directors, can be approved for fraud in the financial statements. For further research is expected to produce more significant results by increasing research data and with different methods